Penyerlahan identiti remaja kesan ketagihan skrin di media sosial - Nor Fazilah Noor Din; Hishamudin Isam (Penerbit Universiti Kebangsaan Malaysia, 2019)
Screen addiction refers to one's inability to control dependency on gadgets, apps, or social media. The global phenomenon is seeing teenagers aged between 13 and 21 years spending a lot of time in cyberspace as one way of realizing their social network on Facebook, Instagram, WeChat, Twitter, Linkin, Tumblr, and blogs. Individuals who face screen addiction problems can affect behavior changes without them being aware. Therefore, this paper examines the issue of screen addiction from a linguistic perspective focusing on youth identity tagging in social media Facebook effects of language use during communication. The study uses this qualitative approach, involving a survey of 1000 Facebook enthusiasts who are experiencing screen addiction based on four criteria set by Social Identity Theory (SIT). The results of the analysis show that young man who are experiencing screen addiction are seen as individuals who have joke element, friendly, competitive, have high confidence and immature, while young girls who belong to the screen addiction group, highlight their identity as an ego, grumpy, fond of chestnut, also have less mature nature. This situation suggests that there is a relationship between the language that teenagers use when communicating with their signaling indirectly.